Basotho Oral Poetry At the Beginning of the Twenty-first Century - Tšiu, M. W. (Moruti William), 1944- (Project Muse, 2019)
This book contains a major research into, and deep investigation of Basotho language oral poetry in Lesotho at the beginning of the twenty-first century. The classical form, the dithoko, which was inspired by tribal wars or battles fought by the Basotho, is explored fully, but the absence of wars, and urbanisation with the economic and social imperatives of modernism, have inspired new forms of poetry. The new forms include dithoko, i.e. 'praise poetry'; the difela, 'mine workers' chants', and the diboko, the latter which as 'family odes', are still performed in rural areas. The research work involved the live performances of 33 diroki, i.e. poets, watched and recorded in their natural environments. The investigators were led by the late Professor Abiola Irele, then of Ohio State University.